2018
DOI: 10.3390/en11081992
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Performance Evaluation of a Wind Turbine Power Output

Abstract: Estimation errors have constantly been a technology bother for wind power management, often time with deviations of actual power curve (APC) from the turbine power curve (TPC). Power output dispersion for an operational 800 kW turbine was analyzed using three averaging tine steps of 1-min, 5-min, and 15-min. The error between the APC and TPC in kWh was about 25% on average, irrespective of the time of the day, although higher magnitudes of error were observed during low wind speeds and poor wind conditions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…However, the actual wind power output is usually more than the theoretically calculated power, as in Equation 2, which may produce an estimation error of about 3%. This is because the gained momentum by the rotating turbine blades sustains the continual rotation when a sudden decrease in wind speed occurs with no major change in the angular wind direction [32]. The output power P(t) quantifies the variable turbine power at each time point t (in minutes).…”
Section: Wind Energy Calculationmentioning
confidence: 99%
“…However, the actual wind power output is usually more than the theoretically calculated power, as in Equation 2, which may produce an estimation error of about 3%. This is because the gained momentum by the rotating turbine blades sustains the continual rotation when a sudden decrease in wind speed occurs with no major change in the angular wind direction [32]. The output power P(t) quantifies the variable turbine power at each time point t (in minutes).…”
Section: Wind Energy Calculationmentioning
confidence: 99%
“…Therefore, the high penetration level of wind turbines and power electronics interfaces will decrease the total system inertia and lower the voltage/frequency stabilization compared to conventional synchronous generating units. The large voltage/frequency deviation might result in separation of the power system [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the operation characteristics of BDFIG in the case of symmetrical grid faults, Equation (11) and (12) are utilized to calculate the compensation term i * cz, and the total reference current i * cd = i * cw + i * cz is finally obtained for the inner CW current controller. Additionally, according to the first equation in (4), E 0 can be obtained as:…”
mentioning
confidence: 99%
“…Wind turbine power output has been studied under themes such as performance characterization [21][22][23], assessment and management [24], estimation/forecast errors [25], and power curves [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…One common conclusion is the presence of deviations of the actual farm or turbine output from that of the supplied power curve using the words errors, dispersion belly and/or variations interchangeably. Abolude & Zhou [24] observed deviations of actual output from the turbine power curve for an 800 kW WT, while Villaneuva & Feijoo [29] argue for a "true power curve" to minimize estimation errors observed from WT real time performance data. In another related study, Whale et al [30] noted deviations of the actual power from manufacturer WTPC for small wind turbines at high wind speeds, and Cooney et al [21] reported similar differences during a performance characterization study for an urban-sited wind turbine.…”
Section: Introductionmentioning
confidence: 99%